Forecasting coconut production in West Aceh Using GIS and SARIMAX - Ridha, Arrazy Elba; Azwanda, Azwanda; Adib, Adib (Journal of Applied Informatics and Computing, 2025)
Coconut (Cocos nucifera) is a strategic commodity for agro-industrial development in Indonesia, especially in Sumatra, which is home to 34.5% of national coconut plantations. One of the major producers, with a coastal geography and tropical climate that is highly suitable for coconut plantations, Aceh Barat, is currently facing the threat of degradation of coconut plantation land loss due to the government's Regional Action Plan for Sustainable Palm Oil Plantations (RAD KSB Aceh 2023-2026). This study aims to look at the total coconut plantation land by integrating geospatial analysis (QGIS) and SARIMAX time series modelling to map coconut plantations in 2024, estimate production trends, and assess the viability of the agro-industry amidst land use conflicts. Results from mapping with QGIS software showed a drastic decrease in coconut area from 3,330.25 hectares in 2022 to 928.2 hectares in 2024. The reduction in coconut plantation area is signalled by RAD KSB's oil palm expansion target of 1,078,728 hectares by 2026. In addition, the results of the mapping obtained several sub-districts with the largest contribution in West Aceh, namely Kaway XVI (234.82 ha) and Muereubo (217.46 ha) of coconut plantation area, while Bubon (16.67 ha) and West Woyla (38.42 ha) experienced significant land conversion. The study also calculated coconut fruit production of 1,229,267 kg (1,229 tonnes) per month from 12 sub-districts, and generated revenue from selling only coconuts of IDR 2.23 billion. SARIMAX forecasts showed high accuracy (RMSE: 700-704; MAPE: 0.19-1.05%) for 10 sub-districts, except Bubon (MAPE: 2.13%) and West Woyla (MAPE: 1.05%) due to data volatility. Furthermore, projections for the next five periods were carried out and obtained results, namely, Period 1 (104,425.88 kg), Period 2 (94,851.07 kg), Period 3 (97,399.50 kg), Period 4 (96,721.21 kg), and Period 5 (96,901.75 kg) which were dominated by stable production in the core area of Kaway XVI: 311,870 kg/month, but volatile in smaller areas. Spatial analysis prioritises Samatiga (58.53 ha) and Arongan Lambalek (79.27 ha) for agro-industrial development, with potential for value-added products.